Diskurser i kartläggning av nyanlända elever - Erika Bomström Aho; Åsa Wedin (Educare)
The aim of this study is to shed light on discourses in national assessment material for recently arrived students and discourses about students' knowledge as they emerge from teachers’ use of the national assessment material for newly arrived students. The empirical material consists of assessment material for five students, two with little or no previous school background and three with long school background. The documentation in the mapping material is analyzed with Gee's discourse analysis. The result shows two different discourses in which information of different kinds is made significant: assessment discourse for newly arrived students and important knowledge at Language Introduction. Through the assessment material, the Swedish National Agency for Education supports a comprehensive assessment where information about students' previous knowledge and background regarding language and education is requested, with a particular focus on numeracy and literacy. What emerges from the study is that the documentation is inconsistent, often fragmentary and abbreviated. The results also show that the teachers consider personal matters, such as fleeing and arriving in Sweden, to be important knowledge at Language Introduction that they need to document. Additionally, the documentation regarding students who have experience studying in formal schools is more informative compared to the documentation for those students who have little or no experience of formal education. Thus, the information which is intended to be provided through assessment material appears only vaguely, and there is a discrepancy as some information is left out, particularly for students with short or no earlier schooling.